SUSTAINABLE CORPORATE ENTREPRENEURSHIP AND FIRM PERFORMANCE: A STUDY ON MALAYSIAN PUBLIC LISTED FIRMS - SERAI, MAJID HUSSAIN (2017)
Research communities in developed economies are paying considerable attention to Corporate Entrepreneurship (CE). In view of the significance of CE, researchers in developing economies are also paying substantial attention to CE. In Malaysia specifically, the adoption of CE activities in large companies is still at a premature stage. Similarly, sustainability has also been getting attention, as emphasised in modern literature by international and local organisations (United Nations, World Bank, Bursa Malaysia). The issue of sustainability is also highlighted to be the tenth Malaysian plan. Sustainability is considered to be essential in the long-term socio-economic and environmental development. In this regard, literature has evolved from entrepreneurship to CE and is currently heading towards “sustainable corporate entrepreneurship” (SCE). CE dimension has also been evolving over the years and there is still room for new dimensions. Therefore, in this study sustainability has been introduced as a new dimension; and by incorporating CE and sustainability, this will significant contribution to the current body of knowledge. Recently, the relationship between CE and firm performance has been examined. However, the results were inconclusive and context-dependent; therefore, further investigation was recommended. The objectives of this study are to examine the relationship between individual dimensions, and between SCE and firm performance. To address the objectives of this study, an SCE framework and index have been developed in this study. Data for this study was gathered from the top Malaysian public listed firms and analysed using SPSS. This research study provides evidence supporting the significant relationship between the SCE and firm performance. In addition, dimensions of SCE such as innovativeness, proactiveness, risk-taking, competitive aggressiveness were found to be significantly related. Similarly, the social and environmental sub-dimensions of sustainability were also significantly related with firm performance. However, the autonomy and economic sub-dimensions of sustainability were insignificantly related with firm performance.